The nerve supply of zygomaticus major: Variability and distinguishing zygomatic from buccal facial nerve branches. Issue 4 (30th January 2018) - Kehrer, A.; Engelmann, S.; Bauer, R.; Taeger, C.; Grechenig, S.; Kehrer, M.; Prantl, L.; Tamm, E. R.; Bleys, R. L. A. W.; Mandlik, V.
Abstract : The zygomaticus major (ZM) is important for the human smile. There are conflicting data about whether the zygomatic or buccal branches of the facial nerve are responsible for its motor innervation. The literature provides no precise distinction of the transition zone between these two branch systems. In this study, a definition to distinguish the facial nerve branches at the level of the body of the zygoma is proposed. In the light of this definition, we conducted an anatomical study to determine how the source of innervation of the ZM was distributed. A total of 96 fresh‐frozen cadaveric facial halves were dissected under loupe magnification. A hemiparotidectomy was followed by antegrade microsurgical dissection. Any branch topographically lying superficial to the zygoma or touching it was classed as zygomatic, and any neighboring inferior branch was considered buccal. The arborization of the facial nerve was diffuse in all cases. In 64 out of 96 specimens (67%, 95% CI: 56% to 76%), zygomatic branches innervated the ZM. Buccal branches innervated ZM in the other 32 facial halves (33%, 95% CI: 24% to 44%). There were no differences in respect of sex or facial side. All facial halves displayed additional branches, which crossed the muscle on its inner surface without supplying it. In 31 specimens, a nerve branch ran superficial to ZM in its cranial third. According to our classification, the zygomaticus major is innervated by zygomatic branches in 67% of cases and by buccal branches in 33%. Clin. Anat. 31:560–565, 2018. © 2018 Wiley Periodicals, Inc.